2018
DOI: 10.1007/s12602-018-9468-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Probiotic Honey Consumption on Metabolic Status in Patients with Diabetic Nephropathy: a Randomized, Double-Blind, Controlled Trial

Abstract: To the best of our knowledge, this study is the first evaluating the effects of probiotic honey intake on glycemic control, lipid profiles, biomarkers of inflammation, and oxidative stress in patients with diabetic nephropathy (DN). This investigation was conducted to evaluate the effects of probiotic honey intake on metabolic status in patients with DN. This randomized, double-blind, controlled clinical trial was performed among 60 patients with DN. Patients were randomly allocated into two groups to receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 39 publications
1
52
1
Order By: Relevance
“…One hypothesis is that probiotics improve glucose level in diabetic patients via inhibition of oxidative stress [41]. Only some studies attempted to evaluate the oxidative stress biomarkers to investigate its potential association with intestinal microbiota on glycemic control [10,14,22,[27][28][29][30][31][32][33][34][35][36]. The reported antioxidant activity in several previous animal studies was shown in particular strains of lactic acid bacteria such as B. lactis, L. acidophilus, L. plantarum and L. casei [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One hypothesis is that probiotics improve glucose level in diabetic patients via inhibition of oxidative stress [41]. Only some studies attempted to evaluate the oxidative stress biomarkers to investigate its potential association with intestinal microbiota on glycemic control [10,14,22,[27][28][29][30][31][32][33][34][35][36]. The reported antioxidant activity in several previous animal studies was shown in particular strains of lactic acid bacteria such as B. lactis, L. acidophilus, L. plantarum and L. casei [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Our initial search yielded 435 articles. After screening abstracts and full texts, 13 randomized clinical trials (RCTs) were included which involved 840 subjects with T2DM [10,14,22,[27][28][29][30][31][32][33][34][35][36]. The number of the initial search results and included studies are shown in Fig.…”
Section: Characteristics Of Included Papersmentioning
confidence: 99%
“…40 In addition, Ejtahed et al 41 It was reported that probiotic honey consumption for 12 weeks among DN patients had beneficial effects on insulin metabolism, total-/HDL-cholesterol, serum hs-CRP, and plasma MDA levels, but did not affect other metabolic profiles. 43 Another study showed that probiotic supplementation had beneficial effects on glycemic control and markers of cardiometabolic risk. 44 A meta-analysis showed that probiotic supplementation decreased serum insulin and insulin resistance, but it had no beneficial effect regarding kidney function, body weight and lipid profiles, with a moderate positive effect regarding some oxidative stress biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that probiotic honey consumption for 12 weeks among DN patients had beneficial effects on insulin metabolism, total‐/HDL‐cholesterol, serum hs‐CRP, and plasma MDA levels, but did not affect other metabolic profiles 43 . Another study showed that probiotic supplementation had beneficial effects on glycemic control and markers of cardiometabolic risk 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of the oligosaccharides in honey are prebiotics [163]. Probiotic honey (honey enriched with probiotics) had a beneficial effect on marks of insulin metabolism and markers of inflammation in subjects with diabetic nephropathy [164]. For ocular use, Aristotle wrote of honey being a salve for sore eyes [165] along with ancient honey remedies for eye disease spans Attica, Europe, India, Asia and Africa [166].…”
Section: Other Functional Foodsmentioning
confidence: 99%